On the Connection Between Zonal Current Variability and Oxygen Supply of the Eastern Tropical North Atlantic Focussing on the North Equatorial Undercurrent - Burmeister, Kristin (2019)
The upwelling regions in the eastern tropical Atlantic and Pacific are co-located with zones of oxygen-poor water masses at intermediate depth. The so-called Oxygen Minimum Zones (OMZs) are a consequence of high biological productivity combined with weak ventilation. Within the last few decades, an expansion of the OMZs was observed. Until now it is unclear to what extent variations of the OMZs are attributed to the anthropogenic climate change or to the natural variability of the climate system. This thesis examines changes of the ventilation of the OMZ in the Eastern Tropical North Atlantic (ETNA) focusing on the variability of the North Equatorial Undercurrent (NEUC). The NEUC has been suggested to act as an important oxygen supply route of the ETNA OMZ. Observational estimates of the mean NEUC strength are uncertain due to the presence of elevated mesoscale activity and models have difficulties in simulating a realistic NEUC. This thesis investigates the intraseasonal to multidecadal variability of the NEUC and its impact on oxygen concentrations in the ETNA based on both, observational data and model output. An unique data set of 24 meridional ship sections and multiyear moored observations along 23°W is used. Furthermore, this thesis analyses the output of a high-resolution Ocean General Circulation Model (OGCM) and performs experiments with a conceptual model. For the first time a multiyear NEUC transport time series is reconstructed from direct velocity observations at about 5°N, 23°W. In contrast to previous studies that were mainly based on model output or hydrographic data, hardly any seasonal cycle of NEUC transports can be found. The NEUC transport variability is instead dominated by sporadic intraseasonal events. Both, observations and model output suggest that, on intraseasonal to interannual time scales, a stronger NEUC is not necessarily associated with a higher oxygen supply of the eastern basin. Idealized experiments with the conceptual model suggest that the impact of NEUC variability on ...